2022
DOI: 10.3390/ma15041365
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of Frictional Vibration Noise Reduction Properties of a Polymer Material by PTFE Particles

Abstract: The insufficient lubrication of the contact interface between moving parts can easily induce severe friction vibration and noise under extreme working conditions, which will threaten the service life and reliability of polymer moving components, including water-lubricated stern tube polymer bearings. Thermoplastic polyurethane (TPU) modified by polytetrafluoroethylene (PTFE) particles was developed. The effects of PTFE on the wear and vibration behaviors of modified TPU sliding against the ZCuSn10Zn2 ring-plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Since PTFE has high melt viscosity, melt mixing techniques such as extrusion and/or mix compounding can lead to the fibrillation of PTFE inside the TPU matrix under appropriate conditions. The existing literature on TPU-PTFE composites has primarily focused on specific aspects, including analyzing wear and vibration behaviors, 29 examining tribological properties, 30 as well as investigating alternative fabrication techniques, such as extrusion and microcellular injection molding. 31 To further advance the understanding of TPU-PTFE nanocomposites, this study employed melt extrusion followed by a compression molding technique to fabricate the TPU-PTFE nanocomposites, providing a new perspective on the processing techniques of these materials and their resulting thermomechanical properties.…”
Section: T H Imentioning
confidence: 99%
See 2 more Smart Citations
“…Since PTFE has high melt viscosity, melt mixing techniques such as extrusion and/or mix compounding can lead to the fibrillation of PTFE inside the TPU matrix under appropriate conditions. The existing literature on TPU-PTFE composites has primarily focused on specific aspects, including analyzing wear and vibration behaviors, 29 examining tribological properties, 30 as well as investigating alternative fabrication techniques, such as extrusion and microcellular injection molding. 31 To further advance the understanding of TPU-PTFE nanocomposites, this study employed melt extrusion followed by a compression molding technique to fabricate the TPU-PTFE nanocomposites, providing a new perspective on the processing techniques of these materials and their resulting thermomechanical properties.…”
Section: T H Imentioning
confidence: 99%
“…Among a wide variety of fillers, poly­(tetrafluoroethylene) (PTFE) can be an attractive choice because of its milky white color and promising tribological characteristics, in particular low friction coefficient and good thermal stability, as well as excellent chemical resistance and high melting point (∼327 °C). It has been observed that TPU-PTFE composites can exhibit improved wear resistance, reduced friction, increased hydrophobicity, and enhanced foamability , compared to neat TPU. Yet, to improve the microstructural morphology and thus the thermomechanical properties of a resulting composite, it is desirable to form a PTFE network in the matrix, which can be achieved with in situ fibrillation. Fibrillation was used by Rizvi et al to reinforce polypropylene (PP) matrix with fibrillated PTFE and manufacture foams of PP-PTFE blends by a foam extrusion process under pressurized CO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study provide some reference value for the development of long-life self-lubricating plain-bearing bushings. Li et al [188] fabricated a thermoplastic polyurethane modified by PTFE particles and studied its lubrication and friction state under the same experimental conditions concluded that the modified TPU had better lubrication performance and a 50% reduction in wear, providing excellent friction reduction. The new polymer material has excellent self-lubrication and friction vibration performance, which is a major break through in energy saving and emission reduction.…”
Section: Analysis Of Wind Power Bearing Lubrication Research Based On...mentioning
confidence: 99%
“…Nam, J. et al [10] studied the relationship between the friction coefficient and friction noise, and it was found that when the friction coefficient was less than 0.15 and there was no debris from obvious wear in the contact area, no friction noise was generated. Li et al [13] studied the influence of polytetrafluoroethylene (PTFE) on the wear and vibration behaviors of modified thermoplastic polyurethane (TPU) sliding against the ZCuSn10Zn2 ring-plates for the vibration and noise of water-lubricated stern tube polymer bearings. The results showed that the lower coefficients of friction (COFs) of modified TPU displayed a small fluctuation amplitude and eliminated vibration waveforms at high vibrational frequencies, which was useful for reducing frictional vibration and noise.…”
Section: Introductionmentioning
confidence: 99%